The influence of gender stereotypes on parents´ decision-making processes while buying toys - Kateryna Martiushenko; Eduard Palovchyk (Trendy v podnikání, 2021)
This paper examines the influence of gender factors and stereotypes in the toy industry by investigating the opinions of parents on Creatable World’s gender-neutral doll. It aims to explore the factors influencing the decisions parents make when choosing toys for their children. The paper uses a mixed research method, combining individual semi-structured in-depth interviews as a qualitative method, and a structured questionnaire as a quantitative method. The qualitative study serves as preliminary research for the quantitative method. It helps to outline the main aspects and factors influencing parents’ purchasing decisions and children’s toy preferences. The quantitative element of the study examines the connection between aspects and factors discovered and is aimed to investigate existing patterns. The results indicate that gender impacts both parents’ purchasing decisions and their perception of children’s toys.